Effect of trichloroacetic acid on iron oxidation: Implications on the control of DBPs and deposits in drinking water. (1st February 2021) - Zhuang, Yuan; Shen, Congcong; Gu, Yifan; Chen, Ruya; Shi, Baoyou
Highlights: TCAA promoted the Fe(II) oxidation resulting in sharper surface. Particles had contrary effects on bacterial richness under anaerobic and aerobic conditions. TFOP had higher affinity for electron-accepting DO. TFOP exhibited the strongest cytotoxicity among FOP and the actual deposits. TCAA in iron particles promoted the generation of OH. Abstract: In drinking water distribution system (DWDS), disinfection byproducts (DBPs) have a large possibility of participating in iron oxidation by dissolved oxygen (DO), which may induce particle structure transformations and increase unknown risks. In this work, the influence of trichloroacetic acid (TCAA, one of the most typical DBPs) on iron oxidation processes was studied, and the potential effects of the resulting α-FeOOH particles were evaluated through two aspects: (i) influence on the bacterial community and (ii) toxicity to human cells. TCAA promoted iron oxidation process through an Fe−O−C linkage, which led to a sharper surface of the particles (TCAA-mediated Fe oxide particles, TFOP) than that without TCAA (Fe oxide particles, FOP). Interestingly, the influence of particles on the richness of bacterial community of drinking water was different under anaerobic and aerobic conditions: under anaerobic conditions, the richness of bacterial community increased with the addition of particles, while under aerobic conditions, the richness of bacterial community decreased. The higher affinity of TFOP for electron-accepting DO than FOP indicated the role of DO on TFOP under aerobic conditions. TFOP exhibited the strongest cytotoxicity among FOP and the actual deposits. DFT calculations confirmed that TCAA in iron particles promoted the adsorption and dissociation of H2 O2 to generate more OH with an obvious decrease in the energy barrier from 1.51 to 0.80 eV. This study indicates the high potential of adverse effects of DBPs on loose deposits in DWDS and gives implications for the control of DBPs and deposits in drinking water. Graphical abstract: DBPs could participate in iron oxidation and induce particle structure transformations with potential risks Image, graphical abstract .